Valuable and rational behaviour and system and evolutionary paradigm of structurization of econom - V. V. Biryukov (Вестник СибАДИ)
The methodology of research of economic processes based on complementarity of the principles of individualism and a holizm is offered. Providing paradigmalny reconsideration of communication of ethics and economy. The cultural and valuable structure is interpreted as special measurement of economy as the system institutional cover forming a framework. It is shown that institutional structuring economy acts as search of an institutional compromise of the interacting diverse subjects within which proceeding from cognitive and mental abilities and negotiation force they reach a consent concerning the fact that the created norms and rules provide formation of fair balance of the inconsistent valuable principles taking into account conditions of their implementation. Relevance and the key directions of realization of value-oriented approach when forming institutional the practician and the solution of practical tasks is reasonable.